2009
DOI: 10.1175/2008waf2007105.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Analyses and Forecasts of Banded Heavy Snow Ingredients and Observed Snowfall

Abstract: North American Mesoscale (NAM) model forecasts of the occurrence, magnitude, depth, and persistence of ingredients previously shown to be useful in the diagnosis of banded and/or heavy snowfall potential are examined for a broad range of 25 snow events, with event total snowfall ranging from 10 cm (4 in.) to over 75 cm (30 in.). The ingredients examined are frontogenetical forcing, weak moist symmetric stability, saturation, and microphysical characteristics favorable for the production of dendritic snow cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…11. Frontogenesis can be seen at 0600 UTC 21 August off the coast of northwest California, with weak F n vector convergence over the coast ranges of northern California and western Oregon and immediately offshore corresponding to upward vertical motions associated with frontogenesis (Evans and Jurewicz 2009). A similar band of low-level frontogenesis can also be seen associated with the Washoe zephyr (Clements et al 2006) over western Nevada.…”
Section: Discussion Of the Dlp: Strengths And Weaknessesmentioning
confidence: 97%
“…11. Frontogenesis can be seen at 0600 UTC 21 August off the coast of northwest California, with weak F n vector convergence over the coast ranges of northern California and western Oregon and immediately offshore corresponding to upward vertical motions associated with frontogenesis (Evans and Jurewicz 2009). A similar band of low-level frontogenesis can also be seen associated with the Washoe zephyr (Clements et al 2006) over western Nevada.…”
Section: Discussion Of the Dlp: Strengths And Weaknessesmentioning
confidence: 97%
“…Despite having a more convective appearance, the accumulated precipitation in D3 is similar to that in D12. Such results are discouraging as higher-resolution forecasts are presumed to provide more accurate QPFs (Novak et al 2008;Evans and Jurewicz 2009). Such may be the case when deterministic forecasts capture the convection and structure of the precipitation system in question, but such was not the case for this event.…”
Section: Discussionmentioning
confidence: 99%
“…Note that multiple forms of instability may simultaneously be present (Schultz and Knox 2007;Novak et al 2010;Schumacher et al 2010). Other ingredients one may consider are whether a u e ridge exists at midlevels (Moore and Blakley 1988;Weisman 1996;Jurewicz and Evans 2004;Moore et al 2005), the relative humidity (RH), and whether temperatures are in the dendrite-growth zone [255-261 K; Rogers and Yau (1989); Evans and Jurewicz (2009)]. Evans and Jurewicz (2009) evaluated operational North American Mesoscale Model (NAM; Janjić et al 2005) forecasts of several banded snow events and found that the forecast accuracy of the ingredients degrades substantially for lead times of 12 h and beyond, a result that suggests that deterministic forecasting may be unreliable for this type of event.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations